AKTUALISASI NILAI PANCASILA DALAM TRADISI HAPUMPUNG MASYARAKAT DAYAK NGAJU DI PULANG PISAU, KALIMANTAN TENGAH - Rusnandar, Nandang; Basori, B; Alamsyah P, Suwardi; Masduki, Aam (ppjbsip, 2023)
Abstract: The rapid development of the times has had a major influence on the assimilation of cultures between different owners in a cultural environment. The concern about losing the original regional cultural identity is an important issue and must be the subject of study, especially concerning community traditions. This research was conducted to explore and identify the hapumpung tradition that grows and develops in the community in Pulang Pisau Regency. This information will be collected and documented based on the classification of its forms and functions in the community. The research data is oral in nature so that the data collection method used in this study is the proficient method, namely collecting data (observing and studying) the conversations of informants about the hapumpung tradition. In its operation, the tapping technique is used as a basic technique, namely by tapping (recording) the informants' confessions/stories about the hapumpung tradition. In this case the writer is the key instrument who makes direct observations and records the data that has been listened to. Recording of informants' stories/confessions can be seen as an advanced technique and is called a recording technique and in this case the participation of the writer is receptive because he only listens to what his interlocutor tells him regarding the hapumpung tradition. The steps taken to analyze the data in this study were to describe the Hapumpung tradition based on the traditional values contained in it in accordance with the customary philosophy of the Dayak tribe in Bereng Kaligu Village and Bahu Palawa Village, Kahayan Hilir District, Pulang Pisau Regency. The Hapumpung tradition is an example of a community tradition that is still sustainable and is maintained by the community. The hapumpung tradition is a real manifestation of human interaction with other fellow human beings and it contains noble values in line with the philosophy of